Epidemiology of Non-Hodgkin Lymphomas in the 20th and at the beginning of the 21st century - A. I. Shevchenko; А. M. Sidorenko; E. R. Krohmalnaya (Zaporozhye State Medical University, 2014)
Aim: to study the dynamics of incidence, mortality, survival of patients with non-Hodgkin lymphomas in the world, Ukraine and Zaporizhzhya region in the 20th and at the beginning of the 21st century. The modern understanding of the etiology and prognostic factors of the disease was considered. Methods and results. In order to study the dynamics of incidence, mortality, survival of patients with non-Hodgkin lymphomas in the world, Ukraine, Zaporizhzhya region in the 20th and early 21st century the review of the specialized literature was conducted. We also considered the current ideas about etiology and risk factors of the disease. Non-Hodgkin lymphomas are complicated and poorly treatable diseases, which are found everywhere, and affect all age groups of people. The peak incidence occurs in the elderly and senile age. Continuing the study of non-Hodgkin lymphomas contributes to a better understanding of this disease, which leads to the reduction in mortality and increased survival of patients with non-Hodgkin lymphomas. Conclusion. So, at the beginning of the 21st century, the non-Hodgkin lymphomas remain to be difficult to prevent, diagnose and treat malignant tumors, the incidence of which continues to increase.